2005
DOI: 10.1063/1.1920627
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of two opposing wall jets

Abstract: Two opposing plane turbulent jet flows along a planar surface interact severely in the collision zone above the stagnation point and thereafter form a plane fountainlike merged jet perpendicular to the surface. Direct numerical simulations have been performed to explore the physics of the turbulence field in the collision zone and in the fountain jet formed as a merger of the two originally countercurrent jet streams. It is observed that the turbulence level is exceptionally high in the collision zone, i.e., j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…It should be pointed out that none of these numerical simulations about the planar opposed jets has predicted the deflecting oscillation. The experimental and numerical studies of the planar wall opposed jets have not reported such kind of deflecting oscillation either, 25,26 a) Author to whom correspondence should be addressed. Electronic mail: liweif@ecust.edu.cn.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that none of these numerical simulations about the planar opposed jets has predicted the deflecting oscillation. The experimental and numerical studies of the planar wall opposed jets have not reported such kind of deflecting oscillation either, 25,26 a) Author to whom correspondence should be addressed. Electronic mail: liweif@ecust.edu.cn.…”
Section: Introductionmentioning
confidence: 99%
“…However, the contribution of the velocity-pressure correlation in the transport equation of turbulence has not been well investigated. In particular, pressure-diffusion transport is expected to become significant for this flow as is suggested by previous studies of the near-wake [11] and the impinging wall-jet [12] which show the remarkable contribution of the pressure-diffusion term in the budget of the turbulent kinetic energy equation.…”
Section: Introductionmentioning
confidence: 56%
“…The flow direction of this jet depends with extreme sensitivity on an even very small dissimilarity in momentum flow rates of the colliding flows. A particularly suitable case was found in colliding wall jets [17][18][19], formed on a common solid surface.…”
Section: Introductionmentioning
confidence: 99%